Pengaruh Ekstrak Kunyit dan Kulit Manggis Terhadap Ekspresi Gen PPARα Pada Retina Model Tikus yang Dinduksi DTL - Yenny Noor; Diana K Jasaputra; Julia W Gunadi; Ronny Lesmana; Riska A Safira (Journal of Medicine and Health, 2023)
A long-term high-fat diet (HFD) was proven to induce metabolic dysfunction and causes various organ inflammation, including the retina. As the regulator of lipid metabolism, PPARa plays a role in retinal lipid metabolism and served as one of the targets for decreasing lipid deposition in the retina. Turmeric and mangosteen peel are Indonesian medicinal herbs with enormous health effects, including antiinflammation and hypolipidemic properties. This study aims to determine the effect of ethanol extract from turmeric and mangosteen peel on PPARa  gene expression in the retina of an HFD-induced rat model. Twenty male Wistar rats were divided into 5 groups: negative control, positive control, turmeric, mangosteen, and fibrate. At the end of the study, total cholesterol and triglyceride levels from the blood were measured. The retina was extracted to conduct Realtime PCR for PPARα gene expression. The result showed a significant difference in triglyceride levels between positive control and turmeric groups, and PPARa gene expression in the retina between the control negative, positive, and turmeric groups, but no significant difference was found in other groups. This study concludes that the extract of turmeric increases the expression of the PPARa gene expression in the retina in an HFD-induced rat model.